Drug Free Sport
The National Center for Drug Free Sport, Inc.® was founded in 1999 by Frank Uryasz, previously director of sports sciences for the National Collegiate Athletic Association (NCAA). The executive staff has more than 50 years of cumulative, professional experience in sports drug testing.